Inhibition of transforming growth factor β1 signaling in resident interstitial cells attenuates profibrotic gene expression and preserves erythropoietin production during experimental kidney fibrosis in mice - Fuchs, Michaela A.A.; Broeker, Katharina A.E.; Schrankl, Julia; Burzlaff, Nicolai; Willam, Carsten; Wagner, Charlotte; Kurtz, Armin (Kidney International, 2021)
Kidney fibrosis is characterized by the development of myofibroblasts originating from resident kidney and immigrating cells. Myofibroblast formation and extracellular matrix production during kidney damage are triggered by various cytokines. Among these, transforming growth factor β1 (TGFβ1) is considered a central trigger for kidney fibrosis. We found a highly upregulated expression of TGFβ1 and TGFβ receptor 2 (TGFβ-R2) mRNAs in kidney interstitial cells in experimental fibrosis. Here, we investigated the contribution of TGFβ1 signaling in resident kidney interstitial cells to organ fibrosis using the models of adenine induced nephropathy and unilateral ureteral occlusion in mice. For this purpose TGFβ1 signaling was interrupted by inducible deletion of the TGFβ-R2 gene in interstitial cells expressing the fibroblast marker platelet derived growth factor receptor-β. Expression of profibrotic genes was attenuated up to 50% in kidneys lacking TGFβ-R2 in cells positive for platelet derived growth factor receptor-β. Additionally, deletion of TGFβ-R2 prevented the decline of erythropoietin production in ureter ligated kidneys. Notably, fibrosis associated expression of α-smooth muscle actin as a myofibroblast marker and deposits of extracellular collagens were not altered in mice with targeted deletion of TGFβ-R2. Thus, our findings suggest an enhancing effect of TGFβ1 signaling in resident interstitial cells that contributes to profibrotic gene expression and the downregulation of erythropoietin production, but not to the development of myofibroblasts during kidney fibrosis.
CRIS-Team Scopus Importer:2021-05-07
Keywords: erythropoietin; experimental kidney fibrosis; PDGFR-β; renal interstitial cells; TGFβ